Identifying the Creative Act in Advertising: A Study on Naïve People's Awareness of Restructuring. (22nd November 2018) - Antonietti, Alessandro; Bonacina, Silvia; Colombo, Barbara; Iannello, Paola
ABSTRACT: This study investigates whether laypersons can distinguish between creative and non‐creative artifacts, identify when creativity emerges, and be aware of the merit to be attributed to those who conceive a creative idea. Study 1 analyzed a creative and a non‐creative version of two advertisements. In the creative version, there was an ideational process of advertising drafts where the first meaning changed, whereas in the non‐creative version the original meaning did not change. Forty undergraduates were asked to judge beauty and originality of each draft and the contribution that graphics managers gave to the outcome. Non‐creative changes did not affect beauty and originality ratings, whereas creative modifications increased originality, but not beauty score. Merit was attributed to the graphics manager who transformed the original meaning. In Study 2, one hundred twenty‐eight participants evaluated four combinations of textual (creative/noncreative) and iconic (creative/non‐creative) elements which were added to the advertisements. Again, the creative, but not the non‐creative, contribution to drafts was acknowledged regarding originality by participants. Findings suggest that people can recognize the presence of creativity when it develops and the restructuring mechanism that supports it.